Android-Based Educational Games for Online Learning at PG/Kindergarten - Untari, Rahmania Sri; Wiguna, Akbar; Andhiarini, Rugaya Meis; Pratama, Arnita Fentrin (Universitas Negeri Malang, 2021)
Technology becomes a part of today’s lifestyles. Improving the quality of memorizing is significantly related to the development of learning resources through technological innovation. Educational games are one of the learning resources that can improve the memorization skills of PG/Kindergarten students. The purpose of this study was to develop an Android-based educational game as learning media and assess their effectiveness. The development model used was the ADDIE model. This research was conducted at Daar Al Husna PG/Kindergarten in Malang. Validation by material and media experts showed that the Android-based educational developed was very good and worthy of use. The effectiveness of the application of this Android-based educational game was assessed through pretest and posttest score